Skjern – storgods og magtcenter fra middelalder til renæssance - Bøgh, Anders; Rasmussen, Carsten Porskrog (Kuml, 2010)
Skjern A mighty manor and center of power from the 14th to the 17th century Skjern Castle is mentioned for the first time in a document from AD 1340, where it appears under the name ‘Karmark.’ This was the name later given to an important subordinate (home) farm. In 1340, the castle was the property of the powerful nobleman Peder Vendelbo, but under the control of the counts of Holstein as part of the ongoing struggles concerning control over Denmark. Peder Vendelbo regained his castle shortly afterwards, and it very probably remained in his family for the remainder of the century, even though nothing is directly known about the castle and estate during this period. The family remained extremely powerful and held very high office. In AD 1400 or 1401, Hans Podebusk, a member of a very powerful family, inherited Skjern through his previous marriage to the late Arine Vendelbo. Another of Peder Vendelbo’s heirs made claims and in 1409 it was arranged that Hans’ son Henning Podebusk and Kirsten Falk, heir to the other claimant, should marry and have Skjern. This arrangement provides us with the information that the estate must have comprised c. 100 tenant farms plus property given to Henning’s sister Johanne. Contrary to his father and the Vendelbos, Henning Podebusk held no high political position. During a war with Holstein, he was taken prisoner in 1431 or 1432 and a very high ransom was demanded. This was probably the primary reason for a drastic decline in the position of the family. After the death of Henning Podebusk, both his widow and four daughters married men of the lower gentry, despite their aristocratic descent, and their properties crumbled. They also lost Skjern, but we do not know how this occurred. From 1464, one of the mightiest men of the time, Lord High Steward Erik Ottesen Rosenkrantz, is known to have been in possession of Skjern. But the actual change of lord very probably happened some years before. In 1474 the king recognised Erik Ottesen as sole proprietor, and during the final years of his life (1495-1503) Skjern was his official residence. Sources dating from c. 1525 and later make it possible to reconstruct the estate at the time of the death of Erik Ottesen Rosenkrantz. It then comprised the entire parishes of Skjern and Vester Velling (c. 40 farms in all) and a further c. 110 farms in the remaining parts of the surrounding districts of Middelsom and Sønderlyng (c. 25% of all farms in the area), plus probably another c. 50 more scattered farms lying further away. Furthermore, the lord of the manor possessed the jus patratus over the two village churches of Skjern and Vester Velling, and these parishes were made a private manorial court district – both privileges highly exclusive in the Denmark of the time. In addition to this, Erik Ottesen Rosenkrantz also functioned as royal district governor (lensmand) of the district. His father had already built up a solid position as governor of 5-6 districts in the area in the 1450s, and control over the three most important of these was passed on to Erik Ottesen. In this way, the private castle of Skjern functioned de facto in the same way as royal castles: as the seat of the royal administration of the district. After the death of Erik Ottesen, the Skjern estate was divided up among many heirs, but the eldest son Niels Eriksen took over the nucleus: Skjern Castle, the properties in the two central parishes with all their pertaining privileges and the position of district governor over the surrounding districts of Middelsom and Sønderlyng. This property and position remained with his heirs until 1562. By that time, the estate was split up among several heirs and its position as seat of royal administration had come to an end. In the subsequent century the castle was given up and the manor completely disintegrated. Even though a new manor was established in 1692, it never regained the size and position it had held from 1340 to 1562. Anders Bøgh Carsten Porskrog Rasmussen Institut for Historie og Områdestudier Aarhus Universitet